Ocupação de habitat em florestas re-emergentes: o caso da Preguiça-de-coleira (Bradypus torquatus, Illiger 1811) em fragmentos de Mata Atlântica no Espírito Santo - Paloma Marques Santos (2015)
The study of occupancy patterns is essential to understand species ecological strategies. Our main goal was identify variables that could influence the maned sloth (Bradypus torquatus) occupancy in re-emerging Atlantic forest fragments. We conducted the research in the municipality of Santa Maria de Jetibá, Espírito Santo, Brazil. We selected 33 points distributed in all landscape, distant 500 m and we plotted two perpendicular trails. We conducted five surveys to verify the presence or absence of the species and collect ten local variable data. We performed two moving windows 500m and 1000m at each sampling station in order to perform the landscape analysis. We choose ten of the 25 variables generated to conduct the occupancy estimates. We calculated the dynamic model and the median c-hat to test the assumptions of closed population and independent points. We performed the model selection using the Akaike Information Criteria. To increment the results, we calculated the model averaging and the accumulative weight. We detected the sloth in 48% of points. The dynamic model indicates the population is closed (==0) and the median c-hat shows a data overdispersion (1.79). In both approaches, we used the ad hoc tests. Only local variables act as environmental filters, with positive associations with the important trees and canopy high and negative with the Habitat Complexity Index (ICH), whereas IT had the higher accumulative weight ((w+(j) = 0.64249). With regard to landscape, the Null model was the better-ranked model (QAICc=78.2979), following by the edge disponibility (QAICc=80.584), with a positive association. Our results demonstrated that the presence of essentials trees to food and rest are extremely, in addition to high canopy are very important to sloths and landscape traits have no influence in sloths occupancy, included the regrowth patches, probably consequence of a landscape with a high forest cover (> 30%) such as Santa Maria de Jetibá. This is a very important evidence that the sloth are flexible in occupy degraded environments and that the secondary growth forest are important to speciess conservation projects.